2017
DOI: 10.1530/eje-16-0620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of AIP and inhibitory G protein alpha 2 proteins on clinical features of sporadic GH-secreting pituitary adenomas

Abstract: We demonstrate, for the first time, that AIP protein expression associates with Ga protein intensities in sporadic somatotropinomas, suggesting a joint regulation on somatostatin signaling. Low AIP level associates with higher proliferative activity and predicts high GH concentrations after long-term follow-up. The AIP mutation rate of 6.8% is fairly high, reflecting the genetic composition of the Finnish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
(81 reference statements)
0
19
0
Order By: Relevance
“…Loss of this inhibitory G protein signal may be permissive for cellular proliferation and tumor growth. A strongly positive correlation between AIP and Gαi-2 protein expression has also been confirmed in sporadic somatotropinomas (73). The complex interplay between AIP and PKA signaling is further supported by the evidence that AIP interacts physically with both the regulatory (R1α) and the catalytic (Cα) subunits of PKA separately, as well as in complex (76).…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 70%
See 1 more Smart Citation
“…Loss of this inhibitory G protein signal may be permissive for cellular proliferation and tumor growth. A strongly positive correlation between AIP and Gαi-2 protein expression has also been confirmed in sporadic somatotropinomas (73). The complex interplay between AIP and PKA signaling is further supported by the evidence that AIP interacts physically with both the regulatory (R1α) and the catalytic (Cα) subunits of PKA separately, as well as in complex (76).…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 70%
“…Different types of pathogenic variants have been described leading to a truncated protein in many cases (11,71). Besides AHR, AIP has multiple other partners, including chaperones, phosphodiesterases, Gαi proteins, survivin, RET, nuclear receptors, such as thyroid hormone receptor β1, estrogen receptor-α, peroxisome proliferator-activated receptor-α, viral proteins and others (11,72,73). The cAMP-PKA signaling pathway is strongly implicated in pituitary tumorigenesis and the loss of AIP in mutated adenomas has been related to increased cAMP signaling through defective inhibitory Gα protein signaling.…”
Section: Aip Mutations In Fipa and Sporadic Pituitary Adenomasmentioning
confidence: 99%
“…The exact mechanisms linking AIP with the cAMP-dependent PKA pathway remain to be fully elucidated. In human AIP mutationpositive PAs, the expression of the G inhibitory protein Gα i-2 was found to be reduced compared to AIP mutationnegative tumours (Tuominen et al 2015), and the expression of AIP was found to be positively associated with that of Gα i-2 also in sporadic AIP mutation-negative PAs (Ritvonen et al 2017). Moreover, while knockdown of Gα i-2 and Gα i-3 led to a significant increase in cAMP in AIP WT cells, this effect was not observed in AIP-knockout cell lines (Tuominen et al 2015), suggesting that the loss of AIP can affect G inhibitory protein function.…”
Section: Aryl Hydrocarbon Receptor-interacting Proteinmentioning
confidence: 88%
“…Recent studies performed on human and mouse somatotrophinomas demonstrated that AIP is essential to maintain relatively low levels of cAMP in normal somatotrophes, and the lack of AIP causes an accumulation of cAMP through defective Gαi-2 signalling, which leads to a downregulation of phosphorylated extracellular signal-regulated kinases 1/2 (p-ERK1/2) and p-CREB (Tuominen et al 2015). This point was supported by the fact that low Gαi-2 levels were observed in sporadic somatotrophinomas with decreased AIP immunoreactivity, and a positive association between AIP and Gαi-2 was found at protein level, which suggests a combined regulation (Ritvonen et al 2017). AIP expression was associated to higher Gαi-2 and lower Ki67.…”
Section: The Role Of Aip and Zac1 In Ssa Response In Somatotrophinomasmentioning
confidence: 93%
“…AIP was found to be associated with Gα13, Gαq and possibly regulate the abundance of Gαi-2 (Nakata et al 2009, Tuominen et al 2015, Ritvonen et al 2017. These interactions could influence multiple signalling pathways, with the Gαi-cAMP pathway being especially relevant regarding somatotroph cells and somatostatin action (see section below).…”
Section: Aryl Hydrocarbon Receptor (Ahr)mentioning
confidence: 99%